PENGARUH INDEPENDENSI, SKEPTISME PROFESIONAL, PENGALAMAN AUDIT, KUALITAS AUDIT, AUDIT TENURE, DAN PROSEDUR AUDIT TERHADAP TANGGUNG JAWAB AUDITOR DALAM MENDETEKSI KECURANGAN PADA LAPORAN KEUANGAN (Studi Empiris pada Auditor Kantor Akuntan Publik di Kota Semarang) - Dian Eka Pratiwi; Abdul Rohman (Diponegoro Journal of Accounting, 2021)
The auditor's responsibility in detecting fraud in the financial statements is an important matter.This study aims to obtain empirical evidence and analyze the factors that influence the responsibility of auditors in detecting fraud in financial reports, namely independence, professional skepticism, audit experience, audit quality, audit tenure and audit procedures. This research was conducted by means of a questionnaire method, which is distributing a list of questions (questionnaire) which will be filled in by external auditor respondents at the Public Accounting Firm in the Semarang area which are listed in the Directory of the Indonesian Public Accountants Association in 2019. The method used for sampling is purposive sampling and the samples obtained were 61 samples spread across 13 KAPs in the Semarang. The analysis method used is multiple linear regression with SPPSS software. The results showed of this study that independence has a significant negative effect on the responsibility of auditors in detecting fraud in financial statements. Professional skepticism, audit experience, audit tenure have a significant positive effect on the auditor's responsibility in detecting fraud in the audit quality report and audit procedures have a positive and insignificant effect on the auditor's responsibility in detecting fraud in the financial statements.